Optimizin Communiy-Based Landslide Emergency Management at Curug Cilember, Indonesia: an ISO 45001-Oriented Approach - Ermanto, Yakin; Nowo, Dwi; Mizuno, Kosuke (LP2M IAIN Palopo, 2025)
This study aimed to evaluate the landslide emergency management system at the Curug Cilember tourist site, Megamendung District, Bogor Regency, with a focus on the role of local community participation and optimization strategies based on ISO 45001 standards. A qualitative descriptive method was applied, using interviews, field observations, and literature studies, with purposively selected informants relevant to the research context. The results show that the emergency management system includes cross-sectoral planning, implementation through simulations and training, and regular evaluations involving community discussions. The findings highlight key supporting factors such as the presence of disaster-resilient village programs, while identifying obstacles including limited coordination, budget constraints, and low public awareness of landslide risks. Optimization strategies involve strengthening emergency communication, providing regular community-based training, improving evacuation infrastructure, and implementing ISO 45001-based procedures. In conclusion, the synergy between tourism managers, local communities, and visitors is essential to establish an effective and sustainable emergency response system that enhances disaster preparedness and community resilience.